EXPERIENCE OF FOREIGN COUNTRIES IN THE FIELD OF IMPLEMENTATION INTELLECTUAL TRANSPORT SYSTEMS - Bakhodirkhodjaevna, Yusupkhodjaeva Gulchehra (International Journal of Psychosocial Rehabilitation, 2020)
The article considers the intelligent transport systems as an intensive way to resolve traffic problems in the leading countries of the world. The paper deals with international experience of Japan, China, the European Union and the United States in the implementation of intelligent transport systems, and the ability to apply this experience in the Uzbekistan, made for institutional change in the implementation of intelligent transport systems.